2017
DOI: 10.19030/iber.v16i3.10006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Metacognitive, Cognitive And Motivational Cultural Intelligence On Behavioral Cultural Intelligence

Abstract: This study investigates the impact of Metacognitive, Cognitive, and Motivational Cultural Intelligence (CQ) on Behavioral Cultural Intelligence (CQ).  In particular, we examine whether cognitive capabilities influence actions and behavior. The results show that 28.4% of the variability in behavioral CQ is explained by metacognitive CQ, cognitive CQ and motivational CQ. Further analysis was done to determine how each of these three dimensions impacts on behavioral CQ.  Results show that only metacognitive and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Motivational and behavioural CI as dimensions of CI and CI itself was found to be significantly correlated with all the factors of virtual team effectiveness. And research indicates that motivational and metacognitive CI impacts behavioural CI (Gooden et al, 2017). However, motivational CI did not enter the regression equation and thus does not predict virtual team effectiveness significantly and only behavioural CI and cultural intelligence itself were found to be predictive of virtual team effectiveness which contradicts the study that reports that CI and its dimensions does not predict virtual team performance (Ng, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Motivational and behavioural CI as dimensions of CI and CI itself was found to be significantly correlated with all the factors of virtual team effectiveness. And research indicates that motivational and metacognitive CI impacts behavioural CI (Gooden et al, 2017). However, motivational CI did not enter the regression equation and thus does not predict virtual team effectiveness significantly and only behavioural CI and cultural intelligence itself were found to be predictive of virtual team effectiveness which contradicts the study that reports that CI and its dimensions does not predict virtual team performance (Ng, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It is even observed to mediate the role of language ability in task performance of individuals engaging in intercultural interactions at work (Presbitero, 2016). Metacognitive and motivational facets have significant impact on behavioural cultural intelligence (Gooden et al, 2017). It is the flexibility of an individual to adapt the verbal and non-verbal behaviours according to the different cultural contexts (Livermore, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although CQ was originally theorized as multidimensional intelligence (Earley and Ang, 2003), scholars have since determined that all four facets of CQ could be interdependent and strongly interconnected (Ang et al, 2015; Bücker et al, 2015). For example, Gooden et al (2017) demonstrate that individuals cannot effectively display verbal and nonverbal behaviors to meet foreigners’ expectations without possessing adequate cultural knowledge and motivation. Moreover, many studies have reported high correlations among CQ dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%